Estudio del sistema local de cooperación internacional en el Cantón Alausí - Borja Crizón, Rodrigo Patricio (2018)
The Politics of the Ecuadorian State with reference to International Cooperation and the assumption of competence by the Decentralized Autonomous Governments, gave the opening for local governments to assume this responsibility some with greater preparation than others. We have the case of Provincial Councils and Municipalities with vast experience and human contingent that facilitates the use of this tool for local development, on the other hand the medium and small Municipalities that have not managed to obtain the resources of the international cooperation to complement the efforts of the local planning In this context, the objective that we propose with this study is to analyze the Local System of International Cooperation, give guidance to the Municipal Government of how the cooperation actors prioritize their projects and create synergies among the partners that result in a coherence of policies and interventions aligned to Territorial planning.